Pengaruh Independensi Auditor, Etika Profesi dan Komitmen Organisasi Terhadap Kinerja Auditor Pemerintah pada Inspektorat Kota Padang - Dewi Zulvia; Ifdil Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is motivated by the performance of the Padang City Inspectorate auditors which is still not optimal in implementing good governance. This is indicated by the cases of violations that have occurred, including corruption. One example is the corruption of the KONI Padang City Grant Fund with the source of the Padang City APBD Fund from 2018 to 2020, which resulted in financial losses for the State and Region of 3,117,003,327,- (BPKP Representative Office of West Sumatra Province, 2022). The purpose of this study is the effect of auditor independence, professional ethics, and organizational commitment on the performance of Government Auditors at the Padang City Inspectorate. This study uses a quantitative method. Data were collected using a questionnaire technique, the respondents of this study were 52 auditors. Four hypotheses were formulated and tested using multiple linear regression analysis. The results of the study indicate that auditor independence has a significant positive effect on auditor performance, professional ethics has a significant positive effect on auditor performance, and organizational commitment has a significant positive effect on auditor performance. Meanwhile, simultaneously auditor independence, professional ethics, and organizational commitment have a significant positive effect on the performance of Government Auditors at the Padang City Inspectorate. Thus, it can be concluded that the four variables are very important to support the performance of the Padang City Inspectorate auditors